Analytical Challenges in Herbal Medicine - Navale Smita A; More Trupti P; Nagtilak Suhas S (Asian Journal of Pharmaceutical Research and Development, 2025)
Herbal medicine has been practiced across cultures for millennia, yet its integration into modern healthcare remains constrained by analytical, regulatory, and validation challenges. Unlike synthetic drugs, herbal formulations are complex mixtures of phytochemicals whose therapeutic efficacy often arises from synergistic interactions. Variability in raw materials—driven by geographic origin, harvesting time, and post-harvest processing—further complicates reproducibility and quality assurance. Conventional analytical techniques such as TLC, HPLC, and GC-MS provide valuable insights but fail to capture the full spectrum of bioactive compounds, while adulteration and contamination pose significant safety risks. Emerging technologies including metabolomics, DNA barcoding, and chemometrics offer promising solutions for authentication, fingerprinting, and multivariate quality control. Case studies on turmeric, ginseng, and ashwagandha highlight the challenges of standardizing phytochemical content and detecting adulterants. Regulatory frameworks differ widely across regions, hindering global harmonization and clinical validation. Advances in sample preparation, GMP protocols, and the integration of AI and machine learning are reshaping herbal analytics, enabling predictive modelling and automated classification. Sustainability, ethical sourcing, and capacity building remain essential to ensure long-term viability. Addressing these challenges through interdisciplinary collaboration and technological innovation will unlock the full therapeutic potential of herbal medicine in global healthcare.